2017
DOI: 10.1002/2017ja023880
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Parametric Instability Induced by X‐Mode Wave Heating at EISCAT” by Wang et al. (2016)

Abstract: In their recent article Wang et al. (2016) analyzed observations from EISCAT (European Incoherent Scatter) Scientific Association Russian X‐mode heating experiments and claimed to explain the potential mechanisms for the parametric decay instability (PDI) and oscillating two‐stream instability (OTSI). Wang et al. (2016) claim that they cannot separate the HF‐enhanced plasma and ion lines excited by O or X mode in the EISCAT UHF radar spectra. Because of this they distinguished the parametric instability excite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 27 publications
3
15
0
Order By: Relevance
“…The temporal behavior of the ion lines and plasma lines spectra presents the similar feature in the X‐mode and O‐mode heating cycles. Then we reply to the comment by Blagoveshchenskaya et al (), henceforth Comment2017, point to point in section 3. A summary is shown in section 4.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…The temporal behavior of the ion lines and plasma lines spectra presents the similar feature in the X‐mode and O‐mode heating cycles. Then we reply to the comment by Blagoveshchenskaya et al (), henceforth Comment2017, point to point in section 3. A summary is shown in section 4.…”
Section: Introductionmentioning
confidence: 70%
“…As seen in Figures and , HFILs present two maxima in the two different altitudes, which are about 20 km apart. The special feature that the ion lines present two maxima in two different altitudes is often observed in a large number of X‐mode heating experiments (Blagoveshchenskaya et al, , , ). Here the special feature is also observed in the O‐mode heating cycle.…”
Section: Observationmentioning
confidence: 80%
See 1 more Smart Citation
“…Compared with the ponderomotive NC feature in O-mode heating experiments, the timescale of NC development was much longer in the X-mode heating experiment reported here. In X-mode heating experiments, the PDI was excited for several seconds and even minutes (Blagoveshchenskaya et al, 2017b;Wang X et al, 2018). This conclusion was reached by observing the temporal evolution of the HF-enhanced plasma lines and ion lines, both of which are signatures of PDI excitation in ionospheric heating experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, considering the ionosphere as a doubly refracting medium with the presence of the magnetic field, PDI and OTSI was expected to be excited only by O mode pump [21,29]. However, Blagoveshchenskaya et al [35] found that the X mode pump could also excite the enhanced down-shifted and up-shifted ion lines and down-shifted plasma line.…”
Section: Introductionmentioning
confidence: 98%